2010
DOI: 10.1016/j.polymer.2010.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Natural rubber-clay nanocomposites: Mechanical and structural properties

Abstract: The mechanical properties of non-vulcanized natural rubber and dialyzed natural rubber-clay nanocomposites have been studied by uniaxial deformations to evaluate the reinforcement efficiency of the clay. We show that while non-rubber molecules contribute to auto-reinforcement, removal of these molecules improves significantly the performance of clay as reinforcement agent. These mechanical properties are discussed in relation to morphological aspects of the clay characterized by TEM and SANS. The nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…This is well consistent with other studies concerning filler filled NR composites [11,47]. For two-dimensional nanofillers, for example, nanoclay or graphene, they tend to orient and align parallel to the stretching direction at a very low strain ratio [9,10,47,64]. During stretching, the NR chains in the glassy rubber will slip along the GO sheets and form stretching and parallel-arraying straight chain [46].…”
Section: 4supporting
confidence: 91%
See 1 more Smart Citation
“…This is well consistent with other studies concerning filler filled NR composites [11,47]. For two-dimensional nanofillers, for example, nanoclay or graphene, they tend to orient and align parallel to the stretching direction at a very low strain ratio [9,10,47,64]. During stretching, the NR chains in the glassy rubber will slip along the GO sheets and form stretching and parallel-arraying straight chain [46].…”
Section: 4supporting
confidence: 91%
“…The excellent mechanical properties of the natural rubber would be attributed to strain-induced crystallization (SIC) [4][5][6]. The reinforcement effect of filler on NR is variously attributed to 'strain amplification' and 'stress transfer' through the filler network [7][8][9]. Nanofillers are of remarkable influence on the strain-induced crystallization of NR because of their strong interfacial interaction with polymer matrix [10].…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study [45], it was explained that a flocculent coagulated both rubber and silicate simultaneous without intercalating into galleries of clay. Further, excellent degree of exfoliation of clay was obtained through dialyzed aqueous rubber in which excess ionic species and other small non-rubber molecules were eliminated [46]. The eliminating process of ions in the aqueous rubber promotes modulus of the resultant product.…”
Section: Co-coagulation Methodsmentioning
confidence: 99%
“…They found that when the shape factor of CNT was applied as approximate 22, the theoretically predicted values were closed to the experimentally measured values. Renzende et al 36 also used the Modified Guth-Gold model to predict the modulus of clay/NR nanocomposites. They found that when the f was equal to 48, the predicted results were well fitted with the experimental results.…”
Section: Effect Of Starch Concentration On the Performances Of Mdi/pmmentioning
confidence: 99%